#### Answer

{-3, 6}

#### Work Step by Step

1. Factor the expression.
$z^{2}$/6 - z/2 - 3 = (z/3 + 1)(z/2 - 3)
2. Apply the zero factor property.
a) z/3 + 1 = 0
b) z/2 - 3 = 0
3. Solve each linear equation.
a) z = -3
b) z = 6
The solutions are {-3, 6}.

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

{-3, 6}

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.